Aquatic and terrestrial proxy evidence for Middle Pleistocene palaeolake and lake‐shore development at two Lower Palaeolithic sites of Schöningen, Germany. (6th May 2021) - Krahn, Kim J.; Tucci, Mario; Urban, Brigitte; Pilgrim, Julien; Frenzel, Peter; Soulié‐Märsche, Ingeborg; Schwalb, Antje
Abstract : The archaeological sites in the open‐cast mine of Schöningen, Germany, represent outstanding archives for understanding Middle Pleistocene interglacial–glacial transitions and human adaption. Aquatic microfossil and pollen assemblages from the 'Reinsdorf sequence', likely correlated to Marine Isotope Stage 9, document environmental changes from a thermal maximum to succeeding glacial conditions recorded in two sequences of excavation sites 12 II and 13 II. Multi‐proxy analyses enable detailed reconstruction of lake‐shore and landscape developments despite variable microfossil preservation in changing carbonate‐ and organic‐rich deposits. Rich aquatic vegetation with abundant charophytes suggests repeated phases with water depths of 0.5–2 m at site 13 II, while even greater temporary depths are deduced for 12 II DB. Mesorheophilic and mesotitanophilic ostracod species indicate stream inflows with medium–low calcium contents of >18 mg Ca L –1 originating from nearby springs. Diatoms point to meso‐eutrophic conditions and an alkaline pH of the lake water. Interglacial conditions with thermophile forests but no aquatic microfossils preserved, suggesting a dry or only temporarily flooded site, mark the beginning of the sequence. Continuous presence of aquatic organisms and overall dominance of small tychoplanktonic diatoms during a subsequent cool steppe phase provide evidence for increased water depths and unstable habitats characterized by erosion and probably prolonged periods of lake ice cover. During the succeeding boreal forest‐steppe phase, surface runoff into the productive, shallow lake decreased due to a more extensive vegetation cover. Concurrently, intensified groundwater input in contact with the nearby salt wall caused elevated salinities. Following a lake level drop, stream inflows and lake levels increased again towards the end of the Reinsdorf sequence and promoted development of a diverse fauna and flora at the lake shore; thereby maintaining an attractive living and hunting environment for early humans during a phase of generally cooler temperatures and landscape instability at the transition into a glacial period.